Climate-driven divergence in plant-microbiome interactions generates range-wide variation in bud break phenology - Ian M. Ware (Nature Portfolio, 2021)
Ian Ware et al. use reciprocal plant population by soil location feedback experiments to show how the soil microbiomes of the narrowleaf cottonwood are influenced by genetic and environmental variation, and how these factors affect foliar phenology. They find a landscape-level feedback between tree populations and their associated soil microbial counterparts. This study contributes to the understanding of the interplay between soil, climate, plant and microbial populations with climate warming.